Caco‐2 cells – expression, regulation and function of drug transporters compared with human jejunal tissue. (5th September 2016) - Brück, S.; Strohmeier, J.; Busch, D.; Drozdzik, M.; Oswald, S.
Abstract: Background: Induction or inhibition of drug transporting proteins by concomitantly administered drugs can cause serious drug–drug interactions (DDIs). However, in vitro assays currently available are mostly for studying the inhibitory potential of drugs on intestinal transporter proteins, rather than induction. Therefore, this study investigated the suitability of the frequently used intestinal Caco‐2 cell line to predict transporter‐mediated DDIs as caused by induction via activation of nuclear receptors. Methods: TaqMan® low density arrays and LC–MS/MS based targeted proteomics were used to evaluate transporter expression in Caco‐2 cells in comparison with jejunal tissue, in culture–time dependence studies and after incubation with different known inducers of drug metabolism and transport. Additionally, studies on ABCB1 function were performed using Transwell® assays with [ 3 H]‐digoxin and [ 3 H]‐talinolol as substrates after incubation with the prototypical inducers rifampicin, St John's wort, carbamazepine and efavirenz. Results: The gene and protein expression pattern of drug transporters in Caco‐2 cells and jejunal tissue differed considerably. For some transporters culture‐time dependent differences in mRNA expression and/or protein abundance could be determined. Finally, none of the studied prototypical inducers showed an effect either on mRNA expression and protein abundance or on the function of ABCB1. Conclusion: Differences in transporter expression in Caco‐2 cells compared with jejunal tissue, as well as expression dependence on culture time must be considered in in vitro studies to avoid under‐ or overestimation of certain transporters. The Caco‐2 cell model is not suitable for the evaluation of DDIs caused by transporter induction. Copyright © 2016 John Wiley & Sons, Ltd.